Perlindungan Hak Berpartisipasi dan Hak untuk Memiliki Akses ke Pelayanan Publik bagi Suku Anak Dalam - Donny Michael (Badan Strategi Kebijakan Hukum, 2014)
One group of Indonesian society is still relatively underdeveloped Remote Indigenous Communities (KAT), one of which is Tribal Children In. The condition is as a result of their limited access in many areas, including the lack of participation in the implementation of public affairs, the right to elect and be elected and the right to have access to public services as stipulated in Article 25 of the International Covenant on Civil and Political Rights (ICCPR). This study aims to (i) determine protection of the right to participate in government and the right to have access to public services for SAD, (ii) determine the local government policy in the protection of the right to participate in government and the right to have access to public services for SAD, and (iii) determine the policy implementation of the protection of participating in government and the right to have access to public services for SAD. This is a descriptive study using a qualitative approach, where the data was obtained through in-depth interviews with multiple informants (the public and the authorities), the study of literature and documents studies. This study chose a case study in data analysis methods. The purpose of the case study is to provide a detailed overview of the background, and character traits that are typical of the case, or the status of individuals who later from typical properties were going to be used as a general thing. While the benefits expected from the implementation of this study is the availability of policy recommendations that can be used by related agencies in an effort to provide protection against the SAD for the right to participate in government and the right to have access to public services.